2007
DOI: 10.1099/ijs.0.64623-0
|View full text |Cite
|
Sign up to set email alerts
|

Methylocystis heyeri sp. nov., a novel type II methanotrophic bacterium possessing ‘signature’ fatty acids of type I methanotrophs

Abstract: A novel species is proposed for two strains of methanotrophic bacteria (H2 T and Sakb1) isolated from an acidic (pH 4.3) Sphagnum peat bog lake (Teufelssee, Germany) and an acidic (pH 4.2) tropical forest soil (Thailand), respectively. Cells of strains H2 T and Sakb1 were aerobic, Gramnegative, non-motile, straight or curved rods that were covered by large polysaccharide capsules and contained an intracytoplasmic membrane system typical of type II methanotrophs. They possessed both a particulate and a soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 26 publications
3
97
0
1
Order By: Relevance
“…The labeling of the MOBspecific PLFA (i.e., not present in other microbes; C16:1o5t and C16:1o8c) is direct evidence for the methane consumption by representatives of the genera Methylomonas/Methylomicrobium/Methylobacter/Methylosarcina (type Ia) (Bodelier et al, 2009), which were also linked to methane consumption in vitro by microarray analyses (Supplementary Figures S5 and S6 and Supplementary Table S1). The PLFA C16:1o8c is also present in two type II strains, isolated from acidic habitats (Dedysh et al, 2007); however, significant incorporation by these species would be mirrored by an increase of labeling of the PLFA C18:1o8c, which they also posses in large amount. In our samples, this did not occur, strengthening the conclusion that type Ia MOB are responsible for incorporation of label in C16:1o8c.…”
Section: Resultsmentioning
confidence: 98%
“…The labeling of the MOBspecific PLFA (i.e., not present in other microbes; C16:1o5t and C16:1o8c) is direct evidence for the methane consumption by representatives of the genera Methylomonas/Methylomicrobium/Methylobacter/Methylosarcina (type Ia) (Bodelier et al, 2009), which were also linked to methane consumption in vitro by microarray analyses (Supplementary Figures S5 and S6 and Supplementary Table S1). The PLFA C16:1o8c is also present in two type II strains, isolated from acidic habitats (Dedysh et al, 2007); however, significant incorporation by these species would be mirrored by an increase of labeling of the PLFA C18:1o8c, which they also posses in large amount. In our samples, this did not occur, strengthening the conclusion that type Ia MOB are responsible for incorporation of label in C16:1o8c.…”
Section: Resultsmentioning
confidence: 98%
“…The fatty acid 16:1o7 received most of the 13 Clabel in our experiment (Figure 3). This fatty acid is common not only in type I methanotrophs but also in ammonia oxidizers, even in one type II methanotroph (Dedysh et al, 2007). Although ammonia oxidizers can oxidize CH 4 and contain the PLFAs 16:0 and 16:1o7 (Roslev and Iversen, 1999), they seem to play no role for CH 4 oxidation in rice field soil (Bodelier and Frenzel, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, great care should be taken in interpreting PLFA data since the PLFA database for methanotrophs is much less extensive than the 16S rRNA and functional gene databases. For example, a recent study showed that Methylocystis heyeri strains (type II methanotrophs) contained large amounts of 16:18c, a PLFA that was previously thought to be associated with type I methanotrophs only (31). In another study, Chen et al suggested that acid tolerant, acidophilic type II methanotrophs may contain PLFAs that are different from their neutral pH counterparts (22).…”
Section: Other Molecular Markers: Lipidsmentioning
confidence: 99%